Measuring the urbanization in Ukrainian regions: current approaches - Gukalova, Irina; Omelchenko, Natalia (Human Geography Journal, 2016)
Proportion of urban population is a traditional indicator of urbanization degree in many countries and regions. However, the process of urbanization in each country has its own specifics. In many post-Soviet countries a share of urban population does not reflect the penetration rate of «urban» conditions, of modern culture and comfort, but reflects concentration of industrial production. The real «urban» living conditions (and also «urban» problems) usually appear in big cities, but in Ukrainian regions there are many much smaller urban settlements, in which the population living can be classified as «semi-rural». Therefore, to evaluate the real penetration of «urban» living conditions in regions more complicated indicators should be used – integral urbanization indices, which include not only the share of urban population, but also the density of urban population and settlements and so on. In the article the approaches for evaluating the urbanization degree of regions of Ukraineare discussed and their approbation based on the 2014 statistics data was done. Calculations show that by such estimates the traditional regional pattern of urbanization degree in regions is changing, although the main trends look very similar.Donetsk region by different approaches remains hyper-urbanized, but variation in urbanization degree between regions by complex calculation is not so high. Regions with small number of large cities and low urban population and settlement density relates to low-ranked in urbanization degree.